Implementation of the therapeutic use of hydroxyurea for sickle cell disease management in resource-constrained settings: a systematic review of adoption, cost and acceptability. Issue 11 (9th November 2020) - Ryan, Nessa; Dike, Lotanna; Ojo, Temitope; Vieira, Dorice; Nnodu, Obiageli; Gyamfi, Joyce; Peprah, Emmanuel
Abstract : Objectives: Mortality associated with sickle cell disease (SCD) is high in many low- and middle-income countries (LMICs). Hydroxyurea, a medicine to effectively manage SCD, is not widely available in resource-constrained settings. We identified and synthesised the reported implementation outcomes for the therapeutic use of hydroxyurea for SCD in these settings. Design: Systematic review. Data sources: PubMed, Embase, Cochrane, Web of Science Plus, Global Health, CINAHL, and PsycINFO were searched February through May 2019 without any restrictions on publication date. Eligibility criteria: We included empirical studies of hydroxyurea for management of SCD that were carried out in LMICs and reported on implementation outcomes. Data extraction and synthesis: Two reviewers independently assessed studies for inclusion, carried out data extraction using Proctor et al. 's implementation and health service outcomes, and assessed the risk of bias using ROBINS-I (Risk Of Bias In Non-randomised Studies - of Interventions). Results: Two cross-sectional surveys (n=2) and one cohort study (n=1) reported implementation of hydroxyurea for SCD management, namely regarding outcomes of adoption (n=3), cost (n=3) and acceptability (n=1). These studies were conducted exclusively among paediatric and adults populations in clinical settings in Nigeria (n=2) or Jamaica (n=1). Adoption is low, as observed through reported provider practices and patient adherence, in part shaped by misinformation and fear of side effects among patients, provider beliefs regarding affordability and organisational challenges with procuring the medicine. There was no difference in the cost of hydroxyurea therapy compared with blood transfusion in the paediatric population in urban Jamaica. Risk of bias was low or moderate across the included studies. Conclusions: This review rigorously and systematically assessed the evidence on implementation of hydroxyurea in resource-constrained settings such as LMICs. Findings suggest that knowledge regarding implementation is low. To address the know-do gap and guide clinical practice, implementation research is needed. Integrating effective interventions into existing health systems to improve hydroxyurea uptake is essential to reducing SCD-associated mortality. PROSPERO registration number: CRD42020155953.